2006
DOI: 10.1097/01.meg.0000224477.51428.32
|View full text |Cite
|
Sign up to set email alerts
|

Screening of the adult population in Iran for coeliac disease: comparison of the tissue-transglutaminase antibody and anti-endomysial antibody tests

Abstract: The minimum prevalence of gluten sensitivity among the general population of northern and southern Iran is 1:104. The best screening test for the detection of GSE in the general population is IgA tTG-Ab.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
65
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(83 citation statements)
references
References 40 publications
2
65
0
2
Order By: Relevance
“…22 The diagnosis of CD was confirmed by serological detection of the AGA and ATTGA. Tissue transglutamase IgA sensitivity is 70%-100%, 23,24 and its specificity is 99%. 24 The sensitivity of IgA AGA is about 80%, while that of IgG AGA is 90-100%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 The diagnosis of CD was confirmed by serological detection of the AGA and ATTGA. Tissue transglutamase IgA sensitivity is 70%-100%, 23,24 and its specificity is 99%. 24 The sensitivity of IgA AGA is about 80%, while that of IgG AGA is 90-100%.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue transglutamase IgA sensitivity is 70%-100%, 23,24 and its specificity is 99%. 24 The sensitivity of IgA AGA is about 80%, while that of IgG AGA is 90-100%. 25,26 Endoscopic intestinal biopsy was not available in the region.…”
Section: Discussionmentioning
confidence: 99%
“…Screening studies show a high prevalence of CD (between 1/130-1/300) among both healthy children and adult populations in European countries (10,31) . In a recent study, the prevalence of CD in 2000 healthy blood donors was found to be 1.3% (1/166-1/104) in Iran (2,42) . Considering the wide range of clinical characteristics of CD, like anemia, osteoporosis, dermatitis herpetiformis, and neurologic problems and critical problems like non-Hodgkin's lymphoma, small bowel adenocarcinoma, esophageal cancer, and melanoma, early analysis of CD is crucial, because it is otherwise related to increased mortality (26,40,43) .…”
Section: Introductionmentioning
confidence: 99%
“…Anti-gliadin anti body has low sensitivity and high false positive results of this test is common. Thus the test hasn't any application for the screening and the primary diagnose of CD [27]. Based on the conducted researches, serologic tests (antiendomysium antibody and tissue Trans glutamines antibody have high sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the conducted researches, serologic tests (antiendomysium antibody and tissue Trans glutamines antibody have high sensitivity and specificity. Also, the existence of this antibody is related to the degree of atrophy of villis [27,28]. In a study that was done in the khoozestan, the prevalence of IgA anti-TTG was reported about 1% in the population [29].…”
Section: Discussionmentioning
confidence: 99%